Mechanical Response and Failure Characteristics of Granite under Unloading Conditions and Its Engineering Application - Peng, Chao; Liu, Yang; Zhu, Mingde; Hou, Kuikui; Liu, Xingquan; Li, Guilin; Yin, Yantian; Liu, Zhen (Periodica Polytechnica Civil Engineering, 2023)
Excavation in engineering significantly changes the initial stress state of rock, which makes rock inevitably in complex unloading conditions, thus it is of great significance to make a profound investigate of the mechanical characteristics of rock under unloading condition. This paper carried out two different stress paths including conventional triaxial compression and unloading confining pressure tests on granite specimen from Sanshandao gold mine, and systematically analyzed the strength characteristics, deformation characteristics and energy evolution laws. Results show that the brittle failure characteristic of granite under unloading confining pressure are more obvious, and the peak strength, axial deformation and other parameters are smaller than those of triaxial compression test. Especially the deformation modulus decreases with the increase of unloading confining pressure, which is no longer a constant parameter in the sense of continuum. Therefore, the unloading-induced weakening coefficient of engineering rock mass is proposed, and the relationship between the coefficient and the reduction ratio of confining pressure is quantified. Then, the unloading-induced weakening algorithm is developed in FLAC3D to simulate the stability of a deep mine stope. It is found that results of the unloading-induced weakening model are much closer to the engineering practice, which has certain theoretical and practical reference significance for the stability analysis of rock mass engineering.